Asian Liver Transplant Network Clinical Guidelines on Immunosuppression in Liver Transplantation. Issue 3 (March 2019) - Tan, Poh Seng; Muthiah, Mark D.; Koh, Tsingyi; Teoh, Yee Leong; Chan, Albert; Kow, Alfred; Zheng, Qishi; Kwon, Choon Hyuck David; Lee, Guan Huei; Lesmana, Cosmas Rinaldi A.; de Villa, Vanessa; Fung, James; et al.
Abstract : Most management guidelines and much of the available clinical trial evidence for immunosuppressants in liver transplantation (LT) pertain to Western practice. While evidence from Western studies may not translate to Asian settings, there is a paucity of Asian randomized controlled trials of immunosuppression in liver recipients. Nonetheless, there are notable differences in the indications and procedures for LT between Western and Asian settings. The Asian Liver Transplant Network held its inaugural meeting in Singapore in November 2016 and aimed to provide an Asian perspective on aspects of immunosuppression following LT. Because of their importance to outcome following LT, the meeting focused on (1) reducing the impact of renal toxicity, (2) hepatocellular carcinoma recurrence, and (3) nonadherence with immunosuppressant therapy.